2008
DOI: 10.1345/aph.1l062
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospitalization and Discontinuity of Medication Therapy Used in the Community Setting in the Netherlands

Abstract: Hospitalization is associated with discontinuity of drugs used in the community setting. Medication stops were observed most frequently. Hospital safety programs should focus attention on medication therapy discontinuities at times of transition to ensure continuity of care in relation to drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…About 6 % of patients whose use was initiated by their GP were referred to psychiatric care at some point during the fi rst treatment episode and about 34 % of all patients who start their antidepressant use in psychiatrist care transit to GP care. Similarly to other studies which have investigated changes related to transition from general practice to hospital [5,11,15] or specialist care [3] , our study indicated that transition in care leads to treatment changes. However, in antidepressant drug users the direction of the transition is of importance.…”
Section: Discussion ▼supporting
confidence: 79%
“…About 6 % of patients whose use was initiated by their GP were referred to psychiatric care at some point during the fi rst treatment episode and about 34 % of all patients who start their antidepressant use in psychiatrist care transit to GP care. Similarly to other studies which have investigated changes related to transition from general practice to hospital [5,11,15] or specialist care [3] , our study indicated that transition in care leads to treatment changes. However, in antidepressant drug users the direction of the transition is of importance.…”
Section: Discussion ▼supporting
confidence: 79%
“…Poor communication between healthcare professionals, patients and carers contribute to these problems. The risks are greatest when care is transferred, from community to hospital care, within the hospital environment, and on discharge to the community or residential care facility …”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Three main causes for discrepancies after hospital discharge are recognized: inaccurate medication charts at admission, poor communication with the next healthcare provider, and insufficient patient involvement. [6][7][8][9][10] The main objective of this study was to investigate the effect of a discharge medication intervention that addresses the three main causes of unintentional discrepancies on the incidence and nature of medication discrepancies in a geriatric population after hospital discharge.…”
Section: Effect Of a Discharge Medication Intervention On The Incidenmentioning
confidence: 99%